PENINGKATAN PARTISIPASI MASYARAKAT DALAM RANGKA MEWUJUDKAN PENDIDIKAN PEDULI DAN BERBUDAYA LINGKUNGAN HIDUP SEKOLAH - Andina Rahmah (PT. Habe Cendekia Utama, 2025)
Higher education institutions have an obligation to meet or beyond expectations in every way because of their function as suppliers of trustworthy human resources. Improving educational standards requires community participation in educational initiatives and activities. We want to better understand the types of community involvement required to enhance the quality and function of the environment via the PBLHS movement in five districts of Banjarmasin City by using fact-based data analysis methodologies and qualitative descriptive approaches. This will assist us in determining what kinds of community conduct are suitable for fostering conscientious school communities and environmental preservation and improvement projects. Encouragement of more local communities to become engaged in school culture care and education is the aim of this outreach. Direct and indirect community involvement is necessary to improve environmental quality and the role that communities and schools play in maintaining and safeguarding it. Promoting the kinds of community involvement that schools may provide to aid in the educational process also requires school partnership. This is still on campus. in understanding cultural education and being mindful of the learning environment.